Newborn screening in mucopolysaccharidoses - Maria Alice Donati; Elisabetta Pasquini; Marco Spada; Giulia Polo; Alberto Burlina (BMC, 2018)
Abstract Newborn screening (NBS) methods and therapeutic options have become increasingly available for mucopolysaccharidoses (MPS), and there is a clear evidence that early intervention significantly improves the outcome. It is recommended that mucopolysaccharidosis type I (MPS I) is included in the US newborn screening panel, and this is currently underway in some NBS programs in the world. The key factors in recommending MPS I for inclusion in NBS are the strongly improved efficacy of early-onset therapy and the improved performance of screening tests. Two studies on MPS I screening have been conducted in Italy. In the Tuscany-Umbria pilot NBS, eight infants were confirmed positive, and alpha-l-iduronidase (IDUA) gene molecular analysis showed that seven had either homozygosity or compound heterozygosity for pseudodeficiency alleles. p.Ala79Thr and p.His82Gln changes were demonstrated in four and three infants, respectively, six of which were of African origin. Only one infant had transitory elevation of urine glycosaminoglycans (GAGs) (by quantitative analysis) and she is in follow-up at the time of writing. In the North East Italy experience, there was one affected newborn for 66,491 screened. In this patient treatment started at 1 month of age. In the North East Italy experience the incidence of pseudodeficiency was very high (1:6044), with a high incidence of pseudodeficiency from patients of African origin. A significant problem that is encountered in the follow-up of infants with abnormal NBS and variants of unknown significance (VUS) on molecular analysis results relates to those who cannot be positively identified as either affected or unaffected. Long-term follow-up of these infants, and of those detected with late-onset disorders, will be essential to document the true risks and benefits of NBS. The availability of treatments in MPS II, IVA, VI, and VII with a better clinical outcome when started early in life, and the availability of a combined multiple assay for MPS, may be a prerequisite for new pilot NBS studies in the near future.